2010
DOI: 10.1523/jneurosci.5831-09.2010
|View full text |Cite
|
Sign up to set email alerts
|

Neuron Dysfunction Is Induced by Prion Protein with an Insertional Mutation via a Fyn Kinase and Reversed by Sirtuin Activation inCaenorhabditis elegans

Abstract: Although prion propagation is well understood, the signaling pathways activated by neurotoxic forms of prion protein (PrP) and those able to mitigate pathological phenotypes remain largely unknown. Here, we identify src-2, a Fyn-related kinase, as a gene required for human PrP with an insertional mutation to be neurotoxic in Caenorhabditis elegans, and the longevity modulator sir-2.1/SIRT1, a sirtuin deacetylase, as a modifier of prion neurotoxicity. The expression of octarepeat-expanded PrP in C. elegans mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 62 publications
0
34
1
Order By: Relevance
“…PrPC/caveolin-1/Fyn signaling is known to be responsible for prion-mediated neurotoxicity (29,30). Some reports showed that inhibition of Fyn kinase activation in PrPC knock-out cells was blocked by PrP(106-126)-induced PrPC/caveolin-1/Fyn signaling and prevented PrPSc-mediated neuronal cell death (19,30).…”
Section: Discussionmentioning
confidence: 99%
“…PrPC/caveolin-1/Fyn signaling is known to be responsible for prion-mediated neurotoxicity (29,30). Some reports showed that inhibition of Fyn kinase activation in PrPC knock-out cells was blocked by PrP(106-126)-induced PrPC/caveolin-1/Fyn signaling and prevented PrPSc-mediated neuronal cell death (19,30).…”
Section: Discussionmentioning
confidence: 99%
“…32 If ectopic BAX expression is able to induce cell of wild-type PrP in mechanosensory neurons did not result in abnormal behavior. 25 These low expressers, cgIs54 and cgIs55, grew and developed normally (data not shown). However, the high expresser lines, cgIs51, cgIs52 and cgIs53, grew significantly slower than non-transgenic and cgIs54, cgIs55 worms.…”
Section: Expressionmentioning
confidence: 91%
“…[22][23][24] Very recently, C. elegans as another non-vertebrate model was also reported showing that expression of an insertional mutation of PrP in mechanosensory neurons resulted in a progressive loss of response to touch. 25 In this study, we describe our effort to characterize transgenic C. elegans that broadly express the mouse PrP in whole neurons as well as selectively in dopamine neurons. These established C. elegans prion models mimic some functional and pathogenic characteristics found in mammals, which might facilitate the identification and characterization of molecules as well as pathways that are involved in prion-associated neuropathogenesis.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%
“…In EAE, a model for multiple sclerosis (MS), overexpression of Sirt1 improves clinical symptoms with less axonal injury [127] . Sirt1 may also protect against neurodegeneration in both nematode and in vitro models of prion toxicity [128][129][130] .…”
Section: Other Neurodegenerative Diseasesmentioning
confidence: 99%